Development of a Student Worksheet Based on Creative Thinking Using Maze Chase Wordwall for Natural and Social Sciences - Luthfitrania, Filaili Desya; Huda, Choirul; Kartinah, Kartinah (Mimbar Sekolah Dasar, 2025)
This study is motivated by observations indicating that students exhibit low creative thinking skills in learning natural and social sciences. Additionally, there is a lack of variation in teaching methods, and the use of technology in learning is not optimal, making this a complex issue. To address these problems, the implementation of creative thinking-based student worksheets with maze chase features is expected to enhance students' creative thinking skills, make the learning process more engaging and interactive, and leverage existing technological potential. This research explores the development of a creative thinking-based student worksheet using the Maze Chase Wordwall platform, following the RD method and the ADDIE research model. Data were collected quantitatively through observations, interviews, questionnaires, and documentation. The study involved a fourth-grade class with a total of 20 students. The results indicate that the Maze Chase Wordwall-based student worksheet provided students with a new and varied learning experience. Furthermore, the integration of technology in natural and social sciences learning increased students' enthusiasm, as they were highly engaged in completing each level of the game. This approach fostered motivation and helped students better understand the evaluation questions presented by educators.